The problem of entanglement: Biases and fallacies in police conflict management - Staller, Mario (International journal of police science & management, 2022)
Cognitive biases have been identified as drivers of the excessive use of force, which has determined current affairs across the globe. In this article, we argue that the police are facing serious challenges in combating these biases. These challenges stem from the nature of cognitive biases, their sources and the fallacies that mislead police professionals in the way they think about them. Based on a framework of expert decision-making fallacies and biases, we argue that these fallacies limit the impact of efforts to mitigate cognitive biases in police conflict management. In order to achieve a systemic understanding of cognitive biases and their detrimental effects, the article concludes that implementing reflexive structures within the police is a crucial prerequisite to effectively reflect on external influences and to limit bias and fallacies from further unfolding in a self-referential loop.